(untitled) (Philological Studies, 2025)
As the most important journal of the Yugoslav avant-garde whose activities transcended the regional area of ​​its origin, Zenit resonated with its poetics, its ideas and its programmatic concepts in the German-speaking area from which it also received important impulses. Especially in its first, constitutive phase of the journal, numerous incentives from the German-speaking area are visible, which weren’t limited exclusively to the conceptual or ideological level but could also be practically traced through numerous artistic collaborations and acquaintances led mainly by Ljubomir Micić, the ideological genius behind Zenit. Given the transgressive nature of avant-garde movements in general and the clearly explicit mutual influences between Zenit and the German-speaking area, this paper will attempt to give an overview of the German impetus behind Zenit and zenitism in its various shapes and forms, as well as to explore how the German avant-garde and especially German expressionism shaped the early development of Zenit and how this transcultural transfer influenced the positioning of zenitism in the context of the network of European avant-gardes.